On the impact of modified urban albedo on ambient temperature and heat related mortality. (1st March 2021) - Santamouris, M.; Fiorito, F.
Highlights: Increase of the albedo causes a temperature drop of 0.09C per 0.1 rise of the albedo. Increased albedo reduces HRM between 0.1 and 4 deaths per day. Mortality drop is in statistically significant with albedo increase and socioeconomic parameters. Abstract: Urban heat island and regional climate change raise the ambient temperature in cities and increase the levels of heat related mortality. Higher albedo values lower the ambient temperature and reduce the impact of excess urban heat on health. The present work reviews and analyses fourteen detailed studies investigating the impact of increased urban albedo on the ambient temperature and heat related mortality. It is found that the real magnitude of the afternoon temperature drop caused by the albedo increase is close to 0.09C per 0.1 rise of the albedo, and it is highly determined by the specific climatic, landscape and layout characteristic of cities. A statistically significant association of the temperature drop with the albedo increase, the greenery and street ratio in cities is found. It is observed that the levels of heat related mortality increase significantly as a function of the population size of the cities and the local poverty levels, Increased urban albedo is found to reduce heat related mortality between 0.1 and 4 deaths per day, corresponding to an average decrease of deaths close to 19.8% per degree of temperature drop, or 1.8% per 0.1 increase of the albedo. Mortality drop is found to be in statistically significant association with the initial heat related mortality levels, albedo increase and socioeconomic parameters like the local poverty levels. Accurate parametric functions to predict the magnitude of the temperature drop and heat mortality reduction are developed.